2022
DOI: 10.3390/jcm11102870
|View full text |Cite
|
Sign up to set email alerts
|

Increased Platelet Reactivity and Proinflammatory Profile Are Associated with Intima–Media Thickness and Arterial Stiffness in Prediabetes

Abstract: Alterations of glucose homeostasis are associated with subclinical vascular damage; however, the role of platelet reactivity in this process has not been fully investigated. In this cross-sectional study, we evaluated the correlation between markers of platelet reactivity and inflammation and markers of vascular disease in subjects with prediabetes. Markers of platelet reactivity such as 11-dehydro-thromboxane B2 urinary levels (11-dh-TXB2) and mean platelet volume (MPV) and inflammatory indexes such as platel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
1
2
0
1
Order By: Relevance
“…Despite the aforementioned limitations, our study was relatively successful in demonstrating a correlation between subtle changes in platelet count and the development of microalbuminuria in prediabetes. Our study results are particularly meaningful given that the literature on platelet dynamics in prediabetes is rare [34,35]. Previous studies on platelets in diabetes have revealed various pathological changes, such as changes in platelet hematocrit, platelet indices, increased intracellular calcium concentration, increased activation, adhesion, reactivity, and turnover of platelets, and increased reticular platelets [36][37][38].…”
Section: Discussionsupporting
confidence: 53%
“…Despite the aforementioned limitations, our study was relatively successful in demonstrating a correlation between subtle changes in platelet count and the development of microalbuminuria in prediabetes. Our study results are particularly meaningful given that the literature on platelet dynamics in prediabetes is rare [34,35]. Previous studies on platelets in diabetes have revealed various pathological changes, such as changes in platelet hematocrit, platelet indices, increased intracellular calcium concentration, increased activation, adhesion, reactivity, and turnover of platelets, and increased reticular platelets [36][37][38].…”
Section: Discussionsupporting
confidence: 53%
“…Although aspirin has been comprehensively used in populations, comparatively, its clinical reports about arterial stiffness are not too many [ 19 , 61 , 62 ], and none of them involve mechanism explanation. It is taken for granted anti-platelet effect duo to direct correlation of platelet activation with arterial stiffness [ 63 , 64 , 65 ]. Recently, several studies propose that the effect of aspirin on improving arterial stiffness is independent of anti-platelet.…”
Section: Discussionmentioning
confidence: 99%
“…The more severe the renal impairment, or the higher the albuminuria, the greater the risk of cardiovascular as well as other complications. Patients with alteration of glucose homeostasis and type 2 diabetes have higher cardiovascular (CV) risk [39]. However, the question of which of the two phenotypes is associated with a higher cardiovascular risk is the focus of this review.…”
Section: Cardiovascular Risk Profile In Dkd Phenotypesmentioning
confidence: 99%